Karakteristik pasien HIV/AIDS koinfeksi tuberkulosis paru di Rumah Sakit XYZ Buleleng - Eric Kurnia Abdillah; Reza Ismail Ismail Abdul Rahman; Lestari Nugrahini; Luh Yesi Angga Natalia Dewi (STIKes Surya Global Yogyakarta, 2022)
Acquired Immunodeficiency Syndrome (AIDS) is a collection of symptoms that arise due to a decrease in the body's immune system caused by the Human Immunodeficiency Virus (HIV). This study aims to determine the characteristics of HIV/ AIDS in doing therapy based on differences in antiretroviral regimens at XYZ Buleleng Hospital. The method used was descriptive observational using a cross sectional approach. Based on the results of a study on the characteristics of HIV/ AIDS sufferers with Pulmonary Tuberculosis co-infection at XYZ Buleleng Hospital for the January–June 2020 period, a sample of 18 people (total sampling) was obtained, the results in this study were that most of the HIV / AIDS patients with Pulmonary TB co-infection were treated at XYZ Bueleleng Hospital,it occurs with the age group of 26-35 years and men are many more than women. Most sufferers work more than they don't work and have less nutritional status based on BMI. The majority of supporting examination results with hemoglobin levels 10 g/ dl, cd4 count 100 cells/ mm3, negative BTA staining results, and have extensive lesions in thoracic photo radiology.